2020
DOI: 10.3390/e22111191
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Factors Contributing to the Severity of Large Truck Crashes

Abstract: Crashes that involved large trucks often result in immense human, economic, and social losses. To prevent and mitigate severe large truck crashes, factors contributing to the severity of these crashes need to be identified before appropriate countermeasures can be explored. In this research, we applied three tree-based machine learning (ML) techniques, i.e., random forest (RF), gradient boost decision tree (GBDT), and adaptive boosting (AdaBoost), to analyze the factors contributing to the severity of large tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 32 publications
3
13
0
Order By: Relevance
“…e vehicle type (size) also significantly affects the probability of crash risk variations, as verified by 0.7% (0.8%) increase of the probability of "DECR" when "FVT � S (LVT � L)" was set as evidence. is was in line with the findings of Lee [30], Andersen et al [29], and Yoo and Green [33] indicating that the large leading vehicles would lead to a greater headway of the following vehicles and thus possibly result in less variations in crash risk as suggested by Ding et al [14,22]. e spatial frequency actually specified the effects of the perceptual markings on crash risk variations, and if it was set as "f s � L," the probability of "DECR" increased by 1.3% as compared with the original frequency.…”
Section: External Conditionssupporting
confidence: 92%
See 1 more Smart Citation
“…e vehicle type (size) also significantly affects the probability of crash risk variations, as verified by 0.7% (0.8%) increase of the probability of "DECR" when "FVT � S (LVT � L)" was set as evidence. is was in line with the findings of Lee [30], Andersen et al [29], and Yoo and Green [33] indicating that the large leading vehicles would lead to a greater headway of the following vehicles and thus possibly result in less variations in crash risk as suggested by Ding et al [14,22]. e spatial frequency actually specified the effects of the perceptual markings on crash risk variations, and if it was set as "f s � L," the probability of "DECR" increased by 1.3% as compared with the original frequency.…”
Section: External Conditionssupporting
confidence: 92%
“…According to the Highway Safety Manual [28] and to the nature of a surface transportation system, roadway crashes can be attributed to a combination of factors: the drivers (human factors), vehicles (vehicular factors), road infrastructure (roadway factors), and surrounding environment. Specifically, vehicle type and carfollowing mode (large/small vehicles following or being followed) are two main vehicular factors that have been widely verified to be influential in crashes and crash risk [14,22,[29][30][31][32][33]. Similarly, the roadway conditions, such as road type/grade, road geometric alignment, and road crosssection features, were extensively considered to account for crashes and crash risk (see eofilatos and Yannis [5]; Mannering et al [3]; and Papadimitriou et al [4] for systematic reviews).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on the Texas Crash Records Information System (CRIS), Li and colleagues [ 10 ] analyzed 85,184 large truck RTC and found that 1.29% of the drivers (N = 1103) were under the influence of alcohol: 241 were classified as involved in serious RTC (incapacitating or fatal crashes), and 862 were classified as involved in non-serious RTC (all crash types excluding incapacitating or fatal crashes).…”
Section: Resultsmentioning
confidence: 99%
“…Considering all studies that used an objective measure and presented disaggregated data, it was possible to calculate the main descriptive statistics concerning the positivity rates for recreational drugs (summarized in Table 4 ). The positivity rates for recreational drugs among drivers involved in a RTC ranged from a low of 0.6% [ 10 ] to a high of 21.33% [ 14 ]; the weighted average (WA) and its confidence interval (95% CI) of the positivity rates to alcohol: WA= 0.84%; 95% CI (0.30–1.84%).…”
Section: Resultsmentioning
confidence: 99%
“…This model outperforms other models as the direction of the negative gradient is followed in order to train the residuals of each iteration, which can avoid the over-fitting problem. Furthermore, the GBDT model has performed well for knowledge discovery in various fields (9,10). The current study is the first time that the artificial intelligence technology, including GBDT, has been used constructing a multiple myeloma early screening model based on a large amount of clinical conventional examination data.…”
Section: Introductionmentioning
confidence: 95%